Problem-Based Learning Model in Learning Islamic Religious Education (Study of Religious Character) Bosowa Bina Insani Bogor Junior School - Rusman, Adang (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to investigate the application of the problem-based learning (PBL) model in the context of Islamic religious education learning in the Bosowa Bina Insani Middle School environment, Bogor, with a special focus on developing students' religious character. The PBL model is considered a learning method that is able to stimulate problem solving, build conceptual understanding, and strengthen spiritual aspects of religious learning. This research uses a qualitative approach with a descriptive analysis approach; in other words, this research attempts to describe a phenomenon that occurs based on facts and information that are related to each other. Research findings show that the application of the PBL model can provide a more interesting and interactive learning experience, motivating students to actively participate in solving problems based on the context of everyday life. Apart from that, the PBL model has also succeeded in increasing understanding of Islamic religious concepts and strengthening students' religious character, such as social concern, integrity, and responsibility. It is hoped that this research can become the basis for developing curriculum and learning strategies that focus on strengthening religious character in the context of Islamic religious education in junior high schools, especially in Bosowa Bina Insani, Bogor. The implications of this research can contribute to efforts to develop religious education that is holistic and relevant to the demands of the times, as well as providing an empirical basis for further research in this field.